Literasi Keuangan Syariah dan Tingkat Kepercayaan Masyarakat Petani Bawang Merah Kabupaten Brebes Menjadi Nasabah Bank Syariah - Ahmad Faqih Udin (Universitas Nusantara PGRI Kediri, 2023)
Islamic financial literacy is a strategic effort to support the government in educating shallot farmers in general to understand Islamic financial products. The purpose of this study is to examine the extent to which the influence of the level of Islamic financial literacy and banking access to Islamic bank financing and its impact. The method in this study uses a quantitative descriptive approach. The data source used is primary data obtained by distributing questionnaires. Respondents taken were residents who work as shallot farmers in the village of Tanjungsari Brebes. The results showed that the different levels of Islamic financial literacy and public trust had no effect on the intention to save in Islamic banks. This gives Islamic banks an indication that the literacy and trust of the shallot farming community influence the intention to save, so Islamic banks must continue to disseminate information to the community, especially the shallot farmers in Wanasari District, Brebes Regency. With the Islamic financial literacy movement both carried out by the Financial Services Authority (OJK) and other financial institutions to find the right solution to accelerate Islamic financial literacy in Brebes district.